2021
DOI: 10.4149/bll_2021_028
|View full text |Cite
|
Sign up to set email alerts
|

Association of multispecific red blood cell alloimmunization with HLA-Class II variants is related to Rh phenotypes

Abstract: It remains unclear, why only some patients form alloantibodies against foreign RBC antigens. Transfusion of red blood cell (RBC) products and pregnancy are the most relevant causes of immunization against RBC alloantigens. Here we investigated the relationship between RBC alloantibodies, Rh phenotype, and HLA phenotype among patients with multiple RBC alloantibodies METHODS: In a group of 124 multi-responders-including both pregnant women and transplant recipients-we analysed the distribution of HLA-Class II v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…High-frequency screening rate of anti-E antibodies in pregnant females makes anti-E one of the main influencing factors of HDFN [25,26]. Diversity of HLA class molecules in individuals have been reported to be important factors influencing RBC alloimmunization [12]. Therefore, HLA genotypes were investigated between RhE The association between HLA-DRB1*09:01 and RhE alloimmunization susceptibility has been reported in our previous study [13].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…High-frequency screening rate of anti-E antibodies in pregnant females makes anti-E one of the main influencing factors of HDFN [25,26]. Diversity of HLA class molecules in individuals have been reported to be important factors influencing RBC alloimmunization [12]. Therefore, HLA genotypes were investigated between RhE The association between HLA-DRB1*09:01 and RhE alloimmunization susceptibility has been reported in our previous study [13].…”
Section: Discussionmentioning
confidence: 92%
“…High‐frequency screening rate of anti‐E antibodies in pregnant females makes anti‐E one of the main influencing factors of HDFN [25, 26]. Diversity of HLA class molecules in individuals have been reported to be important factors influencing RBC alloimmunization [12]. Therefore, HLA genotypes were investigated between RhE responders and non‐responders among Chinese Han pregnant females in this study, with the aim of elucidating relationships between HLA diversity and RhE alloimmunization during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have associated variants of HLA Class II with RBC alloimmunization and whether the inheritance of HLA Class II phenotypes provides susceptibility or protection against the formation of RBC alloantibodies [ 5 , 7 , 15 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. However, only a handful of these studies focused on the SCD population [ 5 , 7 , 15 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies associated RBC alloimmunization with HLA‐DRB1 variants indicating the role of HLA restriction in susceptibility to forming RBC antibodies, particularly in multi‐responders. Maluskova et al demonstrated the association of HLA‐DRB1*15 with multiple antibody responsiveness in relation to Rh phenotypes [ 25 ]. This supported the hypothesis that certain HLA polymorphisms could further increase susceptibility to multi‐responsiveness towards RBC antigens.…”
Section: Introductionmentioning
confidence: 99%